2019
DOI: 10.1158/0008-5472.can-18-2725
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of a Laminin-411–Notch Axis with CRISPR/Cas9 or a Nanobioconjugate Inhibits Glioblastoma Growth through Tumor-Microenvironment Cross-talk

Abstract: There is an unmet need for the treatment of glioblastoma multiforme (GBM). The extracellular matrix, including laminins, in the tumor microenvironment is important for tumor invasion and progression. In a panel of 226 patient brain glioma samples, we found a clinical correlation between the expression of tumor vascular laminin-411 (a4b1g1) with higher tumor grade and with expression of cancer stem cell (CSC) markers, including Notch pathway members, CD133, Nestin, and c-Myc. Laminin-411 overexpression also cor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 50 publications
2
64
0
Order By: Relevance
“…Indeed, a clinical trial is underway utilizing a small molecule HIF-2α inhibitor to teat glioblastoma [7] . Furthermore, as our results indicate a modest additive effect with temozolomide in cell killing and complementary influences on CSC differentiation status, combination therapies that combine chemotherapeutics with HIF-2α silencing or inhibition are an attractive avenue in the pursuit of a therapy that can eradicate the CSCs that drive recurrence of malignant cancers such as glioblastoma [33,34] .…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, a clinical trial is underway utilizing a small molecule HIF-2α inhibitor to teat glioblastoma [7] . Furthermore, as our results indicate a modest additive effect with temozolomide in cell killing and complementary influences on CSC differentiation status, combination therapies that combine chemotherapeutics with HIF-2α silencing or inhibition are an attractive avenue in the pursuit of a therapy that can eradicate the CSCs that drive recurrence of malignant cancers such as glioblastoma [33,34] .…”
Section: Discussionmentioning
confidence: 80%
“…Dynamic interactions among tumor cells, stromal cells, and the ECM is critical for glioma progression. Overexpression of Laminin-411 correlated with shorter survival of GBM patients and its depletion increased survival of host animals 16 . Integrins involve in the activation of transforming growth factor-β and promote invasiveness, angiogenesis, and maintains cancer cell stemness 17 .…”
Section: Introductionmentioning
confidence: 95%
“…They can trigger downstream signaling for different biological processes including migration, adhesion, proliferation, and survival (Durbeej, 2010 ). In GBM, aberrant overexpression of α4 laminins has been described, and a positive correlation between their expression and tumor grade has been described (Sun et al, 2019 ). Particularly, laminin isoform 8 (α 4 β 1 γ 1 , or laminin 411 according to the new nomenclature) appeared overexpressed on GBM blood vessels and surrounding healthy tissue and was linked to higher recurrence and shorter survival (Ljubimova et al, 2001 ; Lathia et al, 2012 ).…”
Section: Role Of Tumor Microenvironment In Glioma Biologymentioning
confidence: 99%
“…Particularly, laminin isoform 8 (α 4 β 1 γ 1 , or laminin 411 according to the new nomenclature) appeared overexpressed on GBM blood vessels and surrounding healthy tissue and was linked to higher recurrence and shorter survival (Ljubimova et al, 2001 ; Lathia et al, 2012 ). Furthermore, inhibition of laminin isoform 8 through CRISPR/Cas9 techniques has proven to suppress Notch pathway, rendering decreased intracranial tumor growth and longer survival in a glioma animal model (Sun et al, 2019 ). Lathia et al ( 2012 ) showed that α2 laminins provided by perivascular non-CSCs and endothelial cells (ECs) were critical for GBM CSC maintenance and proliferation, promoting glioma CSC radioresistance through enhancing DNA repair.…”
Section: Role Of Tumor Microenvironment In Glioma Biologymentioning
confidence: 99%